The impact of quality of nursing care on patient satisfaction: A systematic review - Hermansyah Hermansyah; Dyah Wiji Puspita Sari; Muh Abdurrouf; Iwan Ardian (School of Health Sciences Al-Ma'arif, 2026)
Background: Patient satisfaction is a key indicator of healthcare quality and reflects how patients evaluate the care they receive during treatment. Among the determinants of patient satisfaction, the quality of nursing care has a particularly important role because nurses maintain the most continuous contact with patients across healthcare settings. A systematic synthesis is therefore needed to clarify how the quality of nursing care influences patient satisfaction. Objective: This systematic review aimed to identify, synthesize, and interpret the available evidence on the impact of quality of nursing care on patient satisfaction across various healthcare settings. Methods: This study used a systematic review design. Literature searches were conducted in PubMed, Scopus, ScienceDirect, Google Scholar, and the Directory of Open Access Journals for studies published between 2015 and 2025. The search strategy used combinations of keywords related to nursing care, nursing service quality, and patient satisfaction in English and Indonesian. Studies were included if they examined patients receiving care in hospitals, primary healthcare centers, or clinics and reported patient satisfaction in relation to nursing care. Ten studies met the inclusion criteria and were synthesized narratively. Results: The findings consistently showed that better quality of nursing care was associated with higher patient satisfaction across inpatient, outpatient, primary care, and specialty care settings. Interpersonal dimensions of nursing care, particularly responsiveness, attention, caring behavior, and therapeutic communication, emerged as the most influential contributors to patient satisfaction. Several studies also indicated that patient satisfaction was shaped by contextual factors such as hospital type, educational level, income, and service organization. Conclusion: The quality of nursing care has a meaningful and consistent impact on patient satisfaction across diverse healthcare contexts. Nursing care that is responsive, communicative, caring, and patient-centered contributes substantially to favorable patient evaluations of care.